Efficient reconfigurable techniques for VLSI arrays with 6-port switches. - Wu Jigang (IEEE Transactions on VLSI systems)
This paper proposes an efficient techniques to reconfigure a two-dimensional degradable very large scale integration/wafer scale integration (VLSI/WSI) array under the row and column routing constraints, which has been shown to be NP-complete. The proposed VLSI/WSI array consists of identical processing elements such as processors or memory cells embedded in a 6-port switch lattice in the form of a rectangular grid. It has been shown that the proposed VLSI structure with 6-port switches eliminates the need to incorporate internal bypass within processing elements and leads to notable increase in the harvest when compared with the one using 4-port switches. A new greedy rerouting algorithm and compensation approaches are also proposed to maximize harvest through reconfiguration. Experimental results show that the proposed VLSI array with 6-port switches consistently outperforms the most efficient alternative proposed in literature, toward maximizing the harvest in the presence of fault processing elements.